2019
DOI: 10.3390/plants9010017
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-Q-TOF/MS-Based Metabolomics Approach Reveals the Antifungal Potential of Pinocembroside against Citrus Green Mold Phytopathogen

Abstract: Pinocembroside (PiCB) isolated from Ficus hirta Vahl. fruit was studied herein with the aim to find the potential mechanism for significant inhibition of growth of Penicillium digitatum, a causative pathogen of citrus green mold disease. PiCB substantially inhibited mycelial growth of P. digitatum, with the observed half maximal effective concentration (EC 50 ), minimum inhibitory concentration (MIC), and minimum fungicidal concentration (MFC) of 120.3, 200, and 400 mg/L, respectively. Moreover, PiCB altered h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Three phenolics, namely, luteolin, apigenin, and umbelliferone, were putatively identified by comparison of extracted positive or negative ions with literature data, for which those were the main constituents previously reported [2,3]. Five flavonoid constituents (13)(14)(15)(16)(17) were all detected in EAE, AE, and ME of HFF. Furthermore, pinocembrin-7-O-β-D-glucoside (13), the main antifungal flavonoid, was also detected in CE of HFF.…”
Section: Hplc-qtof-ms Analysis Of Hff Extractsmentioning
confidence: 85%
See 2 more Smart Citations
“…Three phenolics, namely, luteolin, apigenin, and umbelliferone, were putatively identified by comparison of extracted positive or negative ions with literature data, for which those were the main constituents previously reported [2,3]. Five flavonoid constituents (13)(14)(15)(16)(17) were all detected in EAE, AE, and ME of HFF. Furthermore, pinocembrin-7-O-β-D-glucoside (13), the main antifungal flavonoid, was also detected in CE of HFF.…”
Section: Hplc-qtof-ms Analysis Of Hff Extractsmentioning
confidence: 85%
“…Recently, three new monosubstituted benzene derivatives elucidated as (2R) methyl 2-O-β-d-glucopyranosyl-2-phenyl acetate, (2S) 2-O-benzoyl-butanedioic acid-4-methyl ester, and 4-O-benzoyl-quinic acid were initially isolated from the ethanolic extracts of HFF by our group members [8], and one new compound depicted a potent antifungal effect against Penicillium italicum isolated from citrus fruits. Continuing this research, our group members further isolated another three glycosides of flavonone, and pinocembrin-7-O-β-d-glucoside (PCBG) was said to be a major flavonoid in HFF and showed a prominent in vitro antifungal activity against P. italicum and P. digitatum [11,13]. The antifungal mechanism revealed by metabolomics showed that amino acids, lipids, tricarboxylic acid cycle, and ribonucleic acids all participated in the antifungal process [13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study which bore out the antifungal activity of P7G on P. italicum in potato dextrose agar (PDA) media showed that P7G was successful at inhibiting both Penicillium spp. mycelial growth [23,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study which bore out the antifungal activity of P7G on P. italicum in potato dextrose agar (PDA) media showed that P7G was successful at inhibiting both Penicillium spp. mycelial growth [23,28,29]. However, to date, there have been no reports on the antifungal activity and possible action mechanisms of P7G on postharvest pathogenic fungus in citrus fruit, especially those concerning P. italicum, which infects fresh citrus fruit.…”
Section: Introductionmentioning
confidence: 99%